Advancing the ecological narrative: documentation of broadnose sevengill sharks (Notorynchus cepedianus) in South Puget Sound, Washington, USA - Schulte, Jessica M.; Personius, Ethan M.; Lowry, Dayv; Hillier, Lisa; McInturf, Alexandra G.; Chapple, Taylor K. (Frontiers in Marine Science, 2024)
The broadnose sevengill shark (Notorynchus cepedianus) is a large, apex predator found in temperate waters around the world. Yet data on their distribution are limited, with reports of species occurrence typically restricted to specific bays or estuaries where they have been historically observed in high seasonal abundances. The Puget Sound is located in the southern portion of the Salish Sea, a large estuary spanning the border between northwestern Washington state, USA and southwestern British Columbia, Canada, and serves as an economic, cultural, and ecological hub. Until recently, there was only one verified record of broadnose sevengill sharks in the Salish Sea and none in the Puget Sound. However, our recent multi-agency collaborative effort revealed the presence of adult and sub-adult broadnose sevengill sharks in South Puget Sound, extending their previously known range hundreds of kilometers and into a new ecosystem. This work represents the first evidence of a significant presence of these apex sharks within the Salish Sea.